ASPECTOS EVOLUTIVOS E DIFERENCIAÇÃO DE POPULAÇÕES DE Astyanax scabripinnis (CHARACIDAE, INCERTAE SEDIS) - Castro, Jonathan Pena (2012)
The species complex Astyanax scabripinnis are composed by fish with wide geographic distribution. Their populations are often isolated in small streams, separated by thousands of years, making it a very interesting system to study evolution. The use of different markers is crucial, since they allow inferences on the identification of individuals and therefore the study of populations. Thus, three populations isolated from each other of Campos do Jordão - SP, and two of Maringá - PR were analyzed by geometric morphometrics, correlating with data from presence / absence of B chromosomes, karyotypic and cytogenetic data, and reproductive data. Canonical variate analysis (CVA) showed that there are significant differences between populations (p <0.0001). The discriminant function analysis (DFA) between males and females showed intra and interpopulational sexual dimorphism. The separate CVA of males and females from each population also showed significant difference between them. All populations have 2n = 50 chromosomes arranged in 6m+22sm+10st+12a, the only exception was a population from Maringá, where there was 2n = 48 chromosomes, differentiated in 8m+26sm+6st+8a. B chromosome were only found in the population of Campos do Jordão (1850m altitude), confirming previous studies. In a morphometric analysis separated for individuals with and without B chromosomes, the CVA showed difference in body shape. Individuals with B chromosomes have the ventral anterior region less dilated than those without of this chromosomal element. The CVA also showed differences in body shape between 2n = 50 and 2n = 48 populations in Maringa. The fluorescent in situ hybridization showed differences between markers 5S rDNA and 18S rDNA for all populations. The data suggest pre zygotic reproductive isolation between Campos do Jordao populations. The analysis of all data indicates that the populations are differentiated from each other, indicating adaptation to different environments. This reinforces, among other factors, that these populations should represent different species within the species complex A. scabripinnis, followed by independent evolutionary pathways.